Newspaper Coverage of Environmental Stories: A Content Analysis on Selected Newspapers of Assam - Tezashree Islary, (Indian Journal of Mass Communication and Journalism (IJMCJ), 2024)
This study seeks to find out how the newspapers cover the environmental stories. The study employed a content analysis technique and had specifically focused on environment stories between January 2020 to December 2020. It identified 482 environmental stories from the three newspapers i.e. The Assam Tribune, The Sentinel and The Telegraph. The time frame was chosen for the study based on the time when the environmental issues like flood, deforestation, poaching was at the peak. The selected newspaper dailies were the highest circulated English dailies in the region. This study used the technique of content analysis that captures the variables: magnitude and type, news priority and nature. The study concluded that some important environmental topics such as Disaster management, Wildlife conservation, and Pollution issues did not gain much importance in those newspapers. Overall the findings of the study indicate that the issues related to environmental issues are needed to be more exposed to educate the public.